Viajes de verdad, viajes de mentira: literatura de viajes del período helenístico - Gómez Espelosín, Francisco Javier (Revista de Filología Románica, 2006)
This work analyzes the authors – and their approach facing the unknown - and draws the guidelines which represent the axis of the development of the stories, both real or fabulous, about distant worlds still to explore in the Hellenistic period.